Fulfillment of the criteria for diagnosis of cephalo-pelvic disproportion: ACOG guidelines - S. Srisukho (2020)
© 2020 Srisukho et al. Published by IMR Press. Purpose: To determine the proportion of cesarean delivery due to CPD without fulfillment of the criteria for diagnosis. Materials and Methods: The obstetric database, between January 2010 and December 2012, was assessed to identify the records of cesarean delivery due to CPD, and the complete medical records were comprehensively reviewed. The degree of adherence to the guidelines on diagnosis of CPD was determined using the criteria recommended by American Congress of Obstetricians and Gynecologists (ACOG) in 2003 compared with that based on the new ACOG 2014 guidelines. Results: During the study period, 475 women underwent cesarean delivery indicated by CPD. The percentages of cases diagnosed with CPD without fulfilling the criteria recommended by ACOG 2003 and ACOG 2014 were 19.37% (92 cases) and 92.42% (432), respectively. Regarding ACOG 2003, cases with non-adherence to the guidelines were mainly associated with diagnosis in the latent phase (55 cases; 11.58%), missed diagnosis for macrosomia in cases of prelabor cesarean section (25 cases; 5.26%), and unfulfilled criteria for diagnosis in the second stage (7 cases; 1.47%). Conclusion: Approximately 19% based on ACOG 2003 guidelines and 92% based on ACOG 2014 guidelines failed to meet the criteria for diagnosis of CPD, suggesting that strengthening diagnosis may reduce a large number of unnecessary cesarean sections.